Breast imaging for aesthetic surgery: British Society of Breast Radiology (BSBR), Association of Breast Surgery Great Britain & Ireland (ABS), British Association of Plastic Reconstructive and Aesthetic Surgeons (BAPRAS). Issue 11 (November 2018) - Lowes, Simon; MacNeill, Fiona; Martin, Lee; O'Donoghue, Joe M.; Pennick, Mandana O.; Redman, Alan; Wilson, Robin
Summary: This is an overview of the guidelines for breast imaging before and after aesthetic (cosmetic) breast surgery, which includes but is not limited to implants, lipomodelling and mammoplasty procedures. The guidelines are based on a review of the literature and consensus of breast imaging and aesthetic breast surgery specialists. 1. Pre-aesthetic surgery All women should undergo a full breast history and clinical examination. Abnormal or uncertain clinical assessment (e.g. family history or other related risk, breast symptoms and uncertain examination findings) requires specialist breast assessment in a recognised breast facility. Normal clinical assessment in women with no personal or family history of breast cancer or other related risk: ○ < 40 years: Routine preoperative imaging not recommended. ○ ≥ 40 years: Two-view mammography of both breasts recommended provided no mammography in the preceding 12 months. Adjunctive ultrasound (US) may be considered in women with dense breasts. In general, men do not require preoperative breast imaging unless there is a clear clinical indication at the initial assessment. 2. Post-aesthetic surgery Routine breast imaging (e.g. annual breast US or MRI of implants) is not indicated. If clinical concerns arise during aesthetic follow-up, specialist breast assessment in a recognised breast facility is recommended. Mammographic screening should follow National Health Service (NHS) guidelines and be appropriate for a woman's age and breast cancer risk. If breast imaging or breast assessment is required, it should be performed in a designated breast facility with access to specialist breast imaging and a complete breast multidisciplinary team in accordance with national guidelines and recommendations.